Consumer intentions, reactance and the marketing implications of policy induced mergers and acquisitions in financial services - Mensah, K.; Mensah, G.K.; Madichie, N.O.; Awini, G. (International Journal of Bank Marketing, 2021)
Purpose: The purpose of this study is to establish, drawing upon the indirect effects of customer reaction, from an emerging economy perspective, the marketing implications of policy-induced Mergers and Acquisitions (M&A) in Financial Services. Design/methodology/approach: The study employed a quantitative research approach, relying on data from 517 customers of M&A banks in Ghana. A purposeful sampling technique was used in selecting respondents for the study. Hypotheses were tested using structural equation modelling. Findings – A positive and significant relationship between immersive marketing communication and consumer intention is revealed in the study. The presence of consumer reactions highly influenced the relationship. As a public policy tool, forced mergers and acquisitions were found to increase customer reaction. However, when customers are frequently engaged with relevant and consistent marketing communications, through appropriate channels, such reactions would only be partial. Research limitations and implications: Although some of the information was collected, they was not the main focus of our analysis. We acknowledge that, from a sample demographic perspective, the study did not consider certain other confounding factors that could influence customers’ decisions to remain or switch, such as as customers’ level of banking, type of account, income level, banking experiences in relation to service fees, online banking, etc., as these could also potentially influence customers’ reactions. Perhaps these may have to be considered in future studies. Social implications: when timely and relevant marketing communications are targeted at customers who are directly impacted by the M&A process. They would experience a reaction, but only partially. This has a range of marketing implications for policy-induced M&A and its impact on consumer intention, reactance and attitudes towards the new entity. Originality/value: The marketing literature of financial services has been silent on the implications of M&A from a policy-induced perspective. This study, therefore, contributes to theory by highlighting that the “destruction” of brand value of the affected firms is relatively high in a policy-induced M&A and thus increases the level of customer reaction. This is because a regulator enforces M&A, as public policy usually generates high public interest and public discourse, leading to a heightened customer reaction. However, when Immersive marketing communications are targeted at the customers directly impacted by the M&A. would experience reactance, but only partially.
Research Article
Keywords: Mergers and acquisitions; Consumer intention; Financial services marketing